Revival of fallow lands after wheat harvest Crop diversification through greengram and blackgram cultivation - Mukherjee, Pijush Kanti; Dubey, R. P.; Dubey, Jitendra Kumar; Choudhary, V. K.; Chethan, C. R.; Gharde, Yogita; Singh, P. K.; Pawar, Deepak Vishwanath; Sreekanth, Dasari; A., Jamaludheen (Indian Farming, 2025)
For agriculture, land is considered an important basic unit; however, it is a limited resource. As per the land use statistics for 2018-19, a conservative estimate revealed that from the total net sown area of 139.3 million ha, fallow lands (other than current fallow) and current fallow lands comprise 11.63 and 14.53 million ha, respectively. The net sown area of Madhya Pradesh is 15.2 million ha, out of which 1.75 million ha land is categorised as current fallow land and fallow land (other than current fallow). Modern technological components also led to creation of current fallow due to the non-availability of appropriate resources to the farmers and lack of understanding of technical know-how of the technologies. Weeds are considered as an important constraint leading to 37% yield losses if not controlled properly. Empowering the farmers on technical know-how of integrated crop management practices and availability of appropriate resources as critical inputs were the basic objective for revival of under-utilised lands after wheat harvest. Two adjoining villages namely Umariya Choubey and Barauda under Panagar block of Jabalpur district were selected for implementation of the Farmer FIRST Programme. This article describes the successful revival of underutilised lands after wheat harvest through technological intervention and availability of appropriate resources as critical inputs in adopted villages under FFP.